Extraction of Nickel from Morowali Laterite Ore with Hydrochloric Acid (HCl) - I Komang Jati Purnawan; Daud K. Walanda; Mery Napitupulu (Universitas Tadulako, 2022)
This study aims to determine the influence of temperature, leaching time, and the influence of hydrochloric acid concentration in the nickel extraction process, as well as to determine the optimum conditions of the laterite nickel extraction process using the Taguchi method which is influenced by hydrochloric acid concentration, temperature and leaching time. The laterite samples used came from the Bahodopi District, Morowali Regency, Central Sulawesi Province. Quantitative analysis using AAS (Atomic Absorption Spectrophotometer) with variables studied including acid concentrations of 0.5 M, 1 M, and 2 M, temperatures with levels of 30oC, 60oC, and 95oC, and leaching times of 3 hours, 6 hours, and 12 hours. The optimum conditions obtained from the results of the study were at a temperature of 95oC, a leaching time of 12 hours and a concentration of 2 M with the optimum absorbance obtained, namely 0.1635, the optimum concentration of 5.9693 mg /L with a percent of nickel recovery obtained of 1.41%.